A new endophytic fungus, Chrysofolia barringtoniae sp. nov., from Thailand - Nakarin Suwannarach (2018)
© 2016 The Mycological Society of Japan A new species of endophytic fungi, described herein as Chrysofolia barringtoniae, was isolated from leaves of Barringtonia acutangula in Lampang Province, Thailand. Morphological investigations revealed that its conidia are shorter than in Chrysofolia colombiana. Phylogenetic analyses also support the morphological results. A description and an illustration of C. barringtoniae are provided.